Assessment of Speech Development in Children with Cochlear Implants in Republic of Macedonia Using Monosyllabic-Troche Polysyllabic Test (Closed-Set) - Vesna Lazarovska; Marina Davcheva-Chakar (ID Design 2012, 2013)
Background: Electric stimulation of the auditory nerve via cochlear implants has made a great impact on treatment of sensory deafness. Advanced signal processing and stimulation paradigms have led to continuously improved results in speech understanding. Consequently, indication criteria have been extended to patients with profound and severe-to profound hearing loss and limited speech understanding with conventional acoustic amplification. Aim: The aim of this study was to present speech development in subjects with pre-lingually sensorineural hearing loss implanted with a cochlear implant in Republic of Macedonia. Methods: The study included 31 subjects of both sexes and pre-lingual sensorineural hearing impairment. The average age of the implanted patients was 100.4 ± 74.1 months. The speech perception after cochlear implantation was evaluated using the Monosyllabic-Throche Polysyllabic test (MTP) with closed-set words without the aid of lip-reading. The patients should be able to point-to or clearly repeat the pictured words (or objects). Subjects were followed-up in a period of 6, 12 and 24 month post-implantation. Results: Cochran’s Q-test showed a significant difference in identification of monosyllabic,disyllabic and polysyllabic words in patients with cochlear implant during the analyzed period of 24 months. McNemar’s test confirmed that 24 months after implantation the subjects significantly better identified monosyllabic, disyllabic and polysyllabic words in comparison with the time interval at 12 and 6 months. Also, there was a substantial improvement 12 months after cochlear implantation in comparison with the interval at 6 months.
Keywords: impaired hearing; cochlear implant; speech perception; rehabilitation